PELUANG BISNIS ANGKRINGAN DI KOTA PALANGKA RAYA - Hafizi, Muhammad Riza; Oktaviana, Nita (AL-QARDH, 2017)
The people of Palangka Raya city in today's modern era made angkringan as a place of social interaction and place of consumption for all social layers of society. Therefore the authors seen the existence of business opportunities angkringan. Angkringan was a place to buy food and drink "typical". As for the formulation of the problem (1) How the sales strategy angkringan to achieve sales targets? (2) How was the business opportunity of angkringan in Palangka Raya city? (3) How was the feasibility of angkringan business in Palangka Raya city?